3D Hydrogel Evaporator with Vertical Radiant Vessels Breaking the Trade‐Off between Thermal Localization and Salt Resistance for Solar Desalination of High‐Salinity. Issue 36 (7th August 2022) - Liu, Xinghang; Chen, Feixiang; Li, Yuankai; Jiang, Hanjin; Mishra, Debesh Devadutta; Yu, Fang; Chen, Zihe; Hu, Chaoquan; Chen, Yun; Qu, Liangti; Zheng, Weitao
Abstract: Delivering sufficient water to the evaporation surface/interface is one of the most widely adopted strategies to overcome salt accumulation in solar‐driven interfacial desalination. However, water transport and heat conduction loss are positively correlated, resulting in the trade‐off between thermal localization and salt resistance. Herein, a 3D hydrogel evaporator with vertical radiant vessels is prepared to surmount the long‐standing trade‐off, thereby achieving high‐rate and stable solar desalination of high‐salinity. Experiments and numerical simulations reveal that the unique hierarchical structure, which consists of a large vertical vessel channel, radiant vessels, and porous vessel walls, facilitates strong self‐salt‐discharge and low longitudinal thermal conductivity. With the structure employed, a groundbreaking comprehensive performance, under one sun illumination, of evaporation rate as high as 3.53 kg m −2 h −1, salinity of 20 wt%, and a continuous 8 h evaporation is achieved, which thought to be the best reported result from a salt‐free system. This work showcases the preparation method of a novel hierarchical microstructure, and also provides pivotal insights into the design of next‐generation solar evaporators of high‐efficiency and salt tolerance. Abstract : A 3D hydrogel evaporator with vertical radiant vessels (VR‐evaporator) is prepared to surmount the long‐standing trade‐off between thermal localization and salt resistance for solar desalination of high‐salinity, thereby achieving a groundbreaking overall performance.